The cytotoxic effect of baeckea frustescens extracts in eliminating hypoxic breast cancer cells - Shahruzaman, S. H.; Yusof, F. Z.; Maniam, S.; Fakurazi, Sharida; Maniam, S. (BioMed Central, 2021)
Background: Adaptive metabolic response towards a low oxygen environment is essential to maintain rapid tumour proliferation and progression. The vascular network that surrounds the tumour develops an intermittent hypoxic condition and stimulates hypoxia-inducing factors. Baeckea frutescens is used in traditional medicine and known to possess antibacterial and cytoprotective properties. In this study, the cytotoxic efect of B. frutescens leaves and branches extracts against hypoxic human breast cancer (MCF-7) was investigated. Method: The extracts were prepared using Soxhlet apparatus for ethanol and hexane extracts while the water extracts were freeze-dried. In vitro cytotoxic activities of B. frutescens extracts of various concentrations (20 to 160μg/mL) at 24, 48, and 72 hours time points were studied using MTT in chemically induced hypoxic condition andin 3-dimensional in vitro cell culture system. An initial characterisation of B. frutescens extracts was carried out using Fourier-transform Infrared- Attenuated Total Refection (FTIR-ATR) to determine the presence of functional groups. Results: All leaf extracts except for water showed IC50 values ranging from 23 -158 μg/mL. Hexane extract showed the lowest IC50 value (23 μg/mL), indicating its potent cytotoxic activity. Among the branch extracts, only the 70% ethanolic extract (B70) showed an IC50 value. The hexane leaf extract tested on 3- dimensional cultured cells showed an IC50 value of 17.2 μg/mL. The FTIR-ATR spectroscopy analysis identifed various characteristic peak values with different functional groups such as alcohol, alkenes, alkynes, carbonyl, aromatic rings, ethers, ester, and carboxylic acids. Interestingly, the FTIR-ATR spectra report a complex and unique profle of the hexane extract, which warrants further investigation. Conclusion: Adaptation of tumour cells to hypoxia signifcantly contributes to the aggressiveness and chemoresistance of diferent tumours. The identifcation of B. frutescens and its possible role in eliminating breast cancer cells in hypoxic conditions defnes a new role of natural product that can be utilised as an efective agent that regulates metabolic reprogramming in breast cancer.